(untitled) (Research, Society and Development, 2022)
COVID called SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) emerged in late December 2019, which quickly became a global pandemic. COVID-19 is characterized by presenting as an acute respiratory infection that progresses rapidly and can lead the patient to severe or critical conditions. It is aimed to know the scientific evidence on nursing care to patients with COVID-19 in intensive care units in the period from 2020 to 2021. This is a descriptive, exploratory research with a qualitative approach of the Integrative Literature Review (ILR) type. With the emergence of a new disease, there was a need for nursing professionals working in ICUs to make several changes and adaptations necessary to provide assistance to patients and simultaneous protection of professionals. The nursing professionals perform all the care based on scientific evidence and recommendations of the competent organs worldwide and nationally in the fight against COVID-19.